Formation of Key Competencies of Students at a Non-Linguistic University Using the German Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The intensive growth in the volume of scientific and technical information and the constant updating of technologies require specialists to have a very high level of fundamental training, as well as the abilities and skills of self-education, and the ability to engage in the continuous process of improving their qualifications. The article considers the main points of formation of key competencies of students at a non-linguistic university using the German language.